1990
DOI: 10.2118/17424-pa
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Relative Permeabilities for Athabasca Oil Sands

Abstract: An experimental study of Athabasca bitumen/water relative permeabilities revealed little or no temperature effect on the relative permeabilities to water and bitumen over a range of 100 to 250°C [212 to 482°F]. Comparable results were obtained with both steadyand unsteady-state relative permeability measuring techniques. It was determined that the oil-phase relative permeability curve was convex. Measured curves were also compared with those obtained by history matching. IntroductionRelative permeability is on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…Sufi et al (1982) and Miller and Ramey (1985) have concluded that the variations in relative permeability with temperature are probably not related to fundamental flow properties and they are rather related to experimental artifacts. Polikar et al (1990) also stated that it is not possible to predict theoretically what the effect of temperature on relative permeabilities could be, and the results are system specific. Maini and Okazawa (1987) have also concluded that due to several artifacts involved in the experiments no effect of temperature could be justified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sufi et al (1982) and Miller and Ramey (1985) have concluded that the variations in relative permeability with temperature are probably not related to fundamental flow properties and they are rather related to experimental artifacts. Polikar et al (1990) also stated that it is not possible to predict theoretically what the effect of temperature on relative permeabilities could be, and the results are system specific. Maini and Okazawa (1987) have also concluded that due to several artifacts involved in the experiments no effect of temperature could be justified.…”
Section: Resultsmentioning
confidence: 99%
“…After initializing the core, the separator was connected and the imbibitions process was initiated by injecting water at a rate of 0.8 cc/min. This rate was even less than 1 PV/h as recommended by Polikar et al (1990). During the water injection phase, the oil production was recorded versus time, and the pressure differential across the core was monitored as well.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that the obtained relative permeability increased with temperature. Polikar et al (1990) studied the effect of temperature on Athabasca oil sands. They used both steady and unsteady-state methods in the temperature range of 212-482°F and concluded that the results cannot be generalized due to unstable condition and viscous fingering.…”
Section: Introductionmentioning
confidence: 99%